Antitrust Failures: The Internet Giants - Martin Taschdjian; James Alleman (International Telecommunications Society (ITS), 2018)
Facebook, Amazon, Netflix and Google, as well as Twitter – the FANG companies – have transformed society with both positive and negative effects. Soaring consumer access to information, news, social networks, and entertainment has been stimulated by the ever-more ubiquitous and falling prices of broadband services. E-government has transformed the delivery of public services. However, negative effects have likewise been stark. Certainly, there have been huge disruptions caused by e-commerce. State tax collectors are fighting the loss of sales tax collections. Because Facebook and Google can identify you, the ads can be targeted to your specific wants and needs, even creating "wants and needs" based on your profile. So, what the "customer" – you – perceived as free is not. Indeed, you are the commodity being sold to the advertisers. Because Facebook and Google are two-sided markets, their economic rents are "hidden" from the public (and, apparently, from the antitrust authorities) . On the user side of the market, prices are zero – "free." The other side, advertising rates are "hidden." Facebook's and Google's revenues are derived from advertising which appears when you go to their sites. They can extract exorbitant prices for ads, since they are virtually the only source that can target ads directly to potential clients. This paper examines the potential for antitrust cases against Facebook and Google as a response to their perceived threats to consumer privacy, political influences and advertising dominance. The argument for antitrust action against them is based on the following arguments. Formally, their Herfindahl-Hirschman index (HHI) for search is 8,476. Combined they currently control over half of US digital advertising; these companies together have an HHI of 2,024. In terms of "social media" United States share of visits, Facebook and Google's HHI is "highly concentrated" at 2,471. Each has obtained de facto monopoly or oligopolistic power without any concern on the part of government. Their economic rents are "hidden" from the public because their revenues are derived from advertising which appear when you go to their sites. Thus, they can extract exorbitant prices for ads. Facebook and Google Herfindahl-Hirschman indices (HHI) are high, indicating a concentrated market or highly concentrated market by several different definitions of their markets. Nevertheless, no serious antitrust case or legislation has addressed this monopoly power.
Keywords: D4; K2; L1; L2; L5; L9; 330; Advertising; antitrust; competition; internet; media; regulation; pricing; two-sided market